Cooperative Ligands in Dissolution of Gold. Issue 34 (7th June 2021) - Heliövaara, Eeva; Liljeqvist, Henri; Muuronen, Mikko; Eronen, Aleksi; Moslova, Karina; Repo, Timo
Abstract: Invited for the cover of this issue is the group of Timo Repo at the University of Helsinki. The image depicts a ligand‐exchange reaction as a battle between hummingbirds and golden birds, which represent two different thiol ligands. Read the full text of the article at 10.1002/chem.202101028 Abstract : " Gold is a valuable component in electronic waste, but a major barrier towards its efficient recycling is the inability to selectively dissolve gold under mild and benign conditions. In this respect, our gold dissolution research is driven by the world's megatrends, such as resource scarcity and waste management challenges. Dissolution and recycling of noble metals is in the core of a circular economy and the challenge that our topic thiol‐assisted dissolution of gold aspires to solve ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 8668 ff. (DOI: 10.1002/chem.202101028 ).